OPTIMASI KUALITAS MINYAK GORENG KELAPA MELALUI PENGATURAN KONSENTRASI ASAM ASETAT DAN LAMA PEMANASAN - Triani, Rini; Izzata, Nasywa; Devinor, Monica; Hervelly, Hervelly; Marthia, Nabila; Nurhawa, Shalli (Pasundan Food Technology Journal (PFTJ), 2025)
The traditional production of coconut oil utilizes the heating of coconut cream for oil extraction. Prolonged heating can damage the quality, increase fuel consumption, and shorten shelf life. This study focuses on the impact of acetic acid concentration and cooking duration on coconut oil quality. Employing a Factorial Randomized Block Design, two main factors were analyzed: acetic acid concentration (2% and 2.5%) and cooking duration (30, 45, 60 minutes). A control group with 0% acetic acid was also evaluated. Several parameters, such as oil yield, water content, acid number, peroxide value, impurities, and color were analyzed. The analysis of variance showed that each factor: the variation in acetic acid concentration and cooking duration, affected oil quality, but the interaction between them did not. Treatment with 2% acetic acid for 30 minutes yielded the best quality oil (according to the De Garmo method), with a 29% oil yield and superior quality (water content < 1%, Free Fatty Acid content as Lauric Acid (0.27%), and Brightness Value L* 43.68) compared to traditional commercial coconut cooking oil and successfully met several elements of the Indonesian National Standard for coconut cooking oil. Overall, acidification using acetic acid improved the quality of coconut oil, better than the control group, and is able to offer a more efficient and high-quality coconut cooking oil production method.